Public Health Financing in the State of Rio de Janeiro: Overview (2015 to 2018), Challenges, and Reflections - Ferreira Viana, Larissa; da Silva, Gabriel Henrique; Piassi Dias Godói, Isabella (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objectives: To present the allocation of resources in public health in the State of Rio de Janeiro from 2015 to 2018, originating from the National Health Fund, and demons trate the importance of understanding the management of public health resources. Me thods: A quantitative descriptive study based on data extraction from the period 2015 to 2018 available on the National Health Fund (FNS) portal, as well as some regulatory instruments such as the Multiannual Plan (2016-2019), made available on the State Transparency Portal. Results: Based on the data extracted from the FNS, a total of R22,002,986,283.17 was executed for health, with R480,758,737.56 allocated to Pharmaceutical Assistance and R4,428,294,397.74 to Primary Care, equivalent to 2.18% and 20.13%, respectively. In the Pharmaceutical Assistance scenario, the amount budgeted for the quadrennium was R621,551,730.00, but R571,802,443.20 was executed, corresponding to 92%. It is noteworthy that the Farmácia Popular program saw a decrease in the budget from R5 million in 2015 to R2.8 million in 2017. Con clusions: The study reinforces the relevance of the debate surrounding the financing of the Unified Health System (SUS) and the importance of understanding the challenges in the allocation of public health resources, aiming for active management and the consoli dation of a universal and comprehensive SUS.